Effects of paper crates, plastic bowls and duration of storage on egg quality characteristics of laying chicken - Oyeleye, O.O.; Bamidele, S.A.; Ugochukwu, N.H. (Nigerian Journal of Animal Science, 2023)
This study aimed at evaluating the effect of duration and medium of storage on the external and internal qualities of chicken eggs. A total of 210 fresh eggs from the Plymouth Rock layer breed of chicken were purchased from a commercial farm. All eggs for the study were collected the same day and carefully transported to the laboratory. Fifteen eggs each were randomly allotted to each treatment (0 week: fresh eggs; 2 weeks; 4 weeks and 6 weeks respectively) in two storage media (paper crate and plastic bowl). Eggs in each storage medium were replicated three times with five pieces in each replicate. On each sampling day, eggs were weighed, the length and breadth of the eggs were measured, the eggshell thickness was determined, the albumen heights were measured and yolk colour was determined. These measured parameters were conducted at intervals of two weeks for a period of six weeks. All data obtained were subjected to statistical analysis using t-test and analysis of variance (ANOVA) to compare the effects of storage media and duration of storage on parameters measured respectively. As storage time increased, egg weight, albumen height and Haugh unit significantly (p<0.05) decreased (after 2 weeks of storage) while egg length, egg breadth, shell thickness, and egg shape index (ESI) were not significantly affected (P<0.05) in both media. From the results, it is concluded that eggs from laying chickens could be stored for 14 days before deterioration could set in and both media of storage could be used interchangeably.